Synthesis, microstructure and corrosion behavior of compositionally graded Ni-YSZ diffusion barrier coatings on inconel-690 for applications in high temperature environments. (1st May 2018) - Kirubaharan, A.M. Kamalan; Kuppusami, P.; Priya, R.; Divakar, R.; Gupta, M.; Pandit, Dinesh; Ningshen, S.
Highlights: Graded Ni-YSZ nanocomposite coatings have been developed using EB-PVD as diffusion barrier. Compositional analysis of and across the graded Ni-YSZ coatings using EPMA and SIMS studies. Potentiodynamic and EIS study of as-deposited and heat treated Ni-YSZ coating. Enhanced corrosion resistance for the heat treated Ni-YSZ coatings than that of as-deposited Ni-YSZ and YSZ coatings. Abstract: Cubic YSZ coating and compositionally graded Ni-YSZ nanocomposite coating have been developed on Inconel-690 using electron beam physical vapor deposition technique to act as a chemical diffusion barrier. The microstructure and chemical composition of the graded coating have been characterized by X-ray diffraction, atomic force microscopy, scanning electron microscopy, electron probe microanalysis, X-ray photoelectron spectroscopy and secondary ion mass spectroscopy techniques. Electrochemical corrosion study was carried out in 3 M HNO3 medium and it was found that compositionally graded Ni-YSZ coating heat treated at 1273 K in air showed superior corrosion resistance than as-deposited compositionally graded Ni-YSZ and YSZ coatings on Inconel-690 substrate.